Aortodigestive fistulas as a cause of massive bleeding - González Vales, Horacio; Chiossoni, Marta (Cirugía del Uruguay, 2021)
Two cases of digestive hemorrhage, produced by aortic perforation, with a fissure originated in an ateroma plate, are discussed in this paper. In one of the -cases the fistula was aortoesophageal and in the other aorto-duodenal. These accidents are very serious and are generally recognized in the post mortem examination; however suspicion of their existence might lead to diagnosis while the patient is still alive, since onset of hemorrhages is rarely fulminating, and fatal cases are preceded by several repeated hemorrhages.